EVALUASI PELAKSANAAN PROGRAM GLOBAL LEARNING CENTER (GLC) DALAM MENINGKATKAN MUTU TENAGA PENDIDIK DI SD ISLAM AS-SHOFA PEKANBARU - Rini Senawati; Syakdanur Nas; Muhammad Nasir (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2022)
This study aims to get an overview of the implementation of the program Global Learning Center (GLC) held in SD Islam As-Shofa Pekanbaru, in particular regarding: (1) the context of the program's relevance to the needs of the school; (2) Input the program focused on the curriculum, the readiness of the organizers, trainers / instructors, participants readiness and availability of facilities and infrastructure; (3) The training process includes: management and training activities, training schedules, attendance in training, training materials, monitoring implementation, training methods, and barriers to implementation; (4) the results of GLC program which includes; the quantity and quality of participants.This research was a study evaluating using a qualitative approach. The evaluation model used the CIPP model(context, input, process, product) . Data were collected using observation, interview, and documentation. Data source is: principals, instructors, and teachers. The data analysis technique used is descriptive analysis.The results showed that: (1) GLC program relevant to the needs of teachers in implementing the curriculum used in schools .; (2) on the input side, there are 4 of 5 aspects that meet the standards of objective indicators such curriculum, the readiness of the organizers, instructors and the availability of infrastructure, and one aspect that has not met the objective standard of readiness of participants .; 3) the training went well evidenced by the presence of trainees, training materials and methods based on Multiple Intelligence, and monitoring of training activities. While training schedule has not run properly and there are still obstacles in its implementation. 4) and the results of GLC program based on teacher performance report card shows good achievement of learning outcomes, the quality of the lesson plan, and behavior. While creativity is still in a bad position.